Accuracy Testing of Three-Phase kWh Meters in Direct and Indirect Measurement APP Wiring - Yani Kamisa Putri; Akbar Abadi; Muhardika; Roy Bayu Negara; Ahmad Ilyas Putra Riancefi (Asosiasi Dosen Muda Indonesia, 2026)
The reliability of electric power systems depends significantly on the accuracy of electrical energy metering instruments, as measurement errors directly influence consumption records and the fairness of transactions between utilities and customers. This study assesses the accuracy of kilowatt-hour (kWh) meters installed in three-phase Measuring and Limiting Devices (APP), considering both direct measurement configurations at low voltage (LV) and indirect measurement configurations at medium voltage (MV). The methodology includes field measurements of current, voltage, and power, followed by the calculation of kWh meter errors and Current Transformer (CT) errors using the collected data. The findings show that the kWh meter error is 0.27% for direct measurements and −1.78% for indirect measurements, with an average CT error of 1.97%. All measured error values are within the applicable standard tolerance limits; thus, the kWh meters are considered accurate, reliable, and suitable for operational use.